MONTELUKAST AND LEVOCETERIZINE FIXED DOSE COMBINATION-AN EVIDENCE REVIEW: Pharmaceutical Science-Pharmacy Practice - A.ANANDHASAYANAM; BITU CHULLIKKATTIL.A; ZACHARIAH, NANISHA; SARANYA.P; TAMILSELVAN.A (International Journal of Life Science and Pharma Research, 2022)
Indian pharma market is flooded with various fixed drug combinations. Among them, one of the widely used FDC is montelukast + levocetirizine. This is prescribed for the patients of any age group (paediatrics, adults and geriatric) and used as a long term therapy for the treatment of conditions such as prophylaxis, acute and chronic types of asthma, relief of symptoms of seasonal and perennial allergic rhinitis, prevention of exercise induced bronchoconstriction and chronic idiopathic urticaria. It is very essential to check the rational use of this FDC. Generally fixed dose combinations create confusions among physicians, because it contains more than one drug in various doses and it is very difficult to remember all these details and another issue with the FDCs are that the entire FDC cannot be used if the patient is contraindicated to any of the drug in the FDC. And patient specific dose calculation is also difficult with FDCs. There are very less clinical trial data available about the safety and efficacy of this agent. Objective of this review article is to check the rational use of montelukast levocetirizine FDC. To achieve the objective, all the literatures related to montelukast levocetirizine FDC were collected and analysed. The study concluded that some differences are there in the pharmacokinetic parameters of both these agents includes duration of action. In dosing also, levocetirizine dose can vary from 2.5mg to 10mg once daily whereas montelukast dosing is 10mg. Rationality of this FDC can be further supported by more clinical trial data to conform the rationality of these FDC.